Preliminary Evaluation of the Engagement and Effectiveness of a Mental Health Chatbot - Daley, Kate; Hungerbuehler, Ines; Cavanagh, Kate; Claro, Heloísa Garcia; Swinton, Paul Alan; Kapps, Michael (Frontiers in Digital Health, 2020)
Background: Mental health difficulties are highly prevalent yet access to support is impeded by barriers of stigma, cost and availability. These issues are even more prevalent in low- and middle-income countries, and use of digital technology is one way to overcome these barriers. Digital health interventions have been shown to be effective but often struggle with low engagement rates, particularly in the absence of any human support. Chatbots could offer a scalable solution, simulating human support at a lower cost. Objective: To complete a preliminary evaluation of engagement and effectiveness of Vitalk, a mental health chatbot, at reducing anxiety, depression and stress. Methods: Real world data was analysed from 3629 Vitalk users who had completed the first phase of a Vitalk program (‘less anxiety’, ‘less stress’ or ‘better mood’). Programs were delivered through written conversation with the chatbot. Engagement was calculated from the number of responses sent to the chatbot divided by days in the program. Results: Users sent an average of 8.17 responses / day. For all three programs, target outcome scores reduced between baseline and follow up with large effect sizes for anxiety (Cohen's d = -0.85), depression (Cohen's d = -0.91) and stress (Cohen's d =-0.81). Increased engagement resulted in improved post-intervention values for anxiety and depression. Conclusion: This study highlights the potential of a chatbot to reduce mental health symptoms in the general population within Brazil. Whilst findings show promise, further research is required.